2001
DOI: 10.1366/0003702011953487
|View full text |Cite
|
Sign up to set email alerts
|

Phase References and Cell Effects in Photoacoustic Spectroscopy

Abstract: In Fourier transform infrared (FT-IR) photoacoustic spectroscopy, advanced scanning and data-handling techniques have placed increasing emphasis on the phase of the photoacoustic signal. Unfortunately, there is no agreement on the best material to use as a phase reference. We have examined the frequency dependence of the signal from several candidate phase references and found that cell effects dominate the absolute phases and magnitudes observed. The absolute phase is exceptionally fast at low frequencies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5] The sample under investigation is usually put in a sealed cell (photoacoustic cell) containing air (or other gas), in which one wall is a light window. It has been reported that the position of the sample relative to the window has a considerable effect on the PA signal, due to cell walls and window acting as thermal sinks, [6][7][8] which are dependent on the geometric dimensions of the cell. For PA applications that require a quantitative theoretical treatment, this sample-position-dependence effect must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The sample under investigation is usually put in a sealed cell (photoacoustic cell) containing air (or other gas), in which one wall is a light window. It has been reported that the position of the sample relative to the window has a considerable effect on the PA signal, due to cell walls and window acting as thermal sinks, [6][7][8] which are dependent on the geometric dimensions of the cell. For PA applications that require a quantitative theoretical treatment, this sample-position-dependence effect must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The offset in the spectra comes mainly from the different amounts of sample material in the cup between different measurements but also from the different filling heights of the samples in the cup and the different arrangements of the single hairs in the cup. 17,22,23 For a proper data analysis, the offset needs to be corrected. To normalize, every variable (spectral point) was divided by the sum of the value of all variables for the given sample.…”
Section: Resultsmentioning
confidence: 99%
“…Glassy carbon was used as a reference for all measurements because it comes closest to an ideal phase reference. 47 Since the glassy carbon reference absorbs all infrared radiation on its surface, the phase of a sample should lag behind the reference phase over the whole spectral region. A second advantage of using glassy carbon as reference material is the fact that its photoacoustic signal is the same order of magnitude as that of the sample, enabling the reference and sample spectra to be collected at the same amplification.…”
Section: Methodsmentioning
confidence: 99%